2020
DOI: 10.20884/1.jap.2019.21.1.780
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Association in the Exon 3 of MSTN Gene in Batur Sheep

Abstract: The aim of present study was to investigate myostatin gene polymorphism and its association with weaning weight and body weight in Batur sheep, 30 heads of Batur all lambs were fed by concentrated feed. Body weight measured monthly after weaning to the six months of age. DNA Extraction used 200 ul of whole blood samples. To amplify exon 3 region of MSTN gene a specific primer designed using the Primer3 software. The 25 μl volume contained 25 ng of genomic DNA, 12.5 μl 2x Reaction mix of each primer. The cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This value indicates that body length has a moderate influence on sheep's body weight performance. This result is considerably higher than [18], who obtained a correlation coefficient of 0.466 for sheep aged 1.3-1.6 years, and lower [19], who found that body weight had the highest correlation with body length (r = 0.84). The strength of the correlation between body length and body weight is related to the action of the testosterone hormone on the rate of muscle cell growth and increased activity in stimulating bone growth [8].…”
Section: Correlation Between Body Lenght and Body Weightmentioning
confidence: 58%
“…This value indicates that body length has a moderate influence on sheep's body weight performance. This result is considerably higher than [18], who obtained a correlation coefficient of 0.466 for sheep aged 1.3-1.6 years, and lower [19], who found that body weight had the highest correlation with body length (r = 0.84). The strength of the correlation between body length and body weight is related to the action of the testosterone hormone on the rate of muscle cell growth and increased activity in stimulating bone growth [8].…”
Section: Correlation Between Body Lenght and Body Weightmentioning
confidence: 58%
“…The lack of significant differences between the genotypes of most studied traits, according to the Hardy-Weinberg hypothesis, may be attributed to the system of mating (inbreeding) or consanguineous mating, which plays a significant role in the process of gene fixation and consequently does not affect mRNA binding through the splicing process. This, in turn, affects the arrangement of amino acids resulting from the translation process [22].…”
Section: Genotypementioning
confidence: 99%